Curcumin improves adipocytes browning and mitochondrial function in 3T3-L1 cells and obese rodent model - Dandan Zhao; Yanyun Pan; Na Yu; Ying Bai; Rufeng Ma; Fangfang Mo; Jiacheng Zuo; Beibei Chen; Qiangqiang Jia; Dongwei Zhang; Jiaxian Liu; Guanjian Jiang; et al. (Royal Society Open Science, 2021)
Accumulating evidence suggests that mitochondrial dysfunction and adipocyte differentiation promote lipid accumulation in the development of obesity and diabetes. Curcumin is an active ingredient extracted from Curcuma longa that has been shown to exhibit antioxidant and anti-inflammatory potency in metabolic disorders. However, the underlying mechanisms of curcumin in adipocytes remain largely unexplored. We studied the effects of curcumin on adipogenic differentiation and mitochondrial oxygen consumption and analysed the possible mechanisms. 3T3-L1 preadipocytes were used to assess the effect of curcumin on differentiation of adipocytes. The Mito Stress Test measured by Seahorse XF Analyzer was applied to investigate the effect of curcumin on mitochondrial oxygen consumption in 3T3-L1 adipocytes. The effect of curcumin on the morphology of both white and brown adipose tissue (WAT and BAT) was evaluated in a high-fat diet-induced obese mice model. We found that curcumin dose-dependently (10, 20 and 35 µM) induced adipogenic differentiation and the intracellular fat droplet accumulation. Additionally, 10 µM curcumin remarkably enhanced mature adipocyte mitochondrial respiratory function, specifically, accelerating basic mitochondrial respiration, ATP production and uncoupling capacity via the regulation of peroxisome proliferator-activated receptor γ (PPARγ) (p < 0.01). Curcumin administration also attenuated the morphological changes in adipose tissues in high-fat diet-induced obese mice. Moreover, curcumin markedly increased the mRNA and protein expressions of mitochondrial uncoupling protein 1 (UCP1), PPARγ, peroxisome proliferator-activated receptor-γ coactivator-1α (PGC-1α) and PR domain protein 16 (PRDM16) in vivo and in vitro. Collectively, the results demonstrate that curcumin promotes the adipogenic differentiation of preadipocytes and mitochondrial oxygen consumption in 3T3-L1 mature adipocytes by regulating UCP1, PRDM16, PPARγ and PGC-1α expression.